Markets for Cotton By-Products Global Trends and Implications for African Cotton Producers - Baffes, John (The World Bank, 2010)
This paper analyzes and compares the structure of cotton by-products industries in se-lected countries (Uganda, Tanzania, Benin, and Burkina Faso) in the context of the global vegetable oil market. It reaches several conclusions. First, because the markets for various edible oils are highly integrated with each other, examination of each oil market should be done in conjunction with all other (relevant) edible oil markets. Second, the recent surge in demand for commodities used as feedstocks for biofuels is unlikely to become a new source of growth for the cotton oil market. Third, within the context of deepening the on-going reform efforts in West and Central African countries, cotton by-products should be taken into consideration, both in terms of the cotton price setting mechanism and the size of the organization of the cotton by-products industry. Fourth, trade policies including export bans or import tariffs to protect the domestic crushing industries, and policies that favor crude over refined oils, should be rationalized. Fifth, large cottonseed processing operations using advanced technology, while efficient from a technological perspective, tend not to be economically profitable in the African context. Last, research efforts for new cotton varieties should consider the value of by-products, not just lint